The ECB's fight against low inflation: On the effects of ultra-low interest rates - Ad van Riet (International Journal of Financial Studies, 2017)
Starting in June 2014, the European Central Bank (ECB) stepped up its monetary accommodation in order to counter a too prolonged period of low inflation in the euro area. This article offers a narrative of the monetary policy measures taken up to December 2016 and a review of the effects of ultra-low interest rates. The exceptional monetary stimulus transmitted to the economy broadly as intended. Moreover, it enhanced the financial capacity of economic agents to bear risks. At the same time, the ECB and the European micro- and macro-prudential authorities remained watchful of the unintended side-effects of an extended period of very low or negative interest rates for financial intermediation, financial stability and market discipline and took preventive or corrective measures as appropriate. A joint plan of action carried out by the 19 member countries with the aim to speed up balance sheet repair, accelerate the economic recovery and achieve higher productivity growth could have contributed to a more effective euro area macroeconomic and financial policy mix.
Keywords: E31; E5; G1; G2; 330; ECB monetary policy; quantitative easing; negative interest rates; financial stability